Evaluation of Intrinsic Biomechanical Risk Factors in Patellar Tendinopathy: A Retrospective Radiographic Case-Control Series. Issue 12 (18th December 2018) - Dan, Michael J.; McMahon, James; Parr, William C.H.; Broe, David; Lucas, Phil; Cross, Meryvn; Walsh, William R.
Background: Patellar tendinopathy is an overuse condition often affecting athletes. It has been postulated that patellar tendinopathy is associated with patella alta; however, this and any other anatomic risk factors have not been identified. Purpose: To explore whether lever arm differences from radiographic measurements exist between patients with and without tendinopathy. This may provide surgeons with a simple radiographic means to identify patients at risk. Study Design: Cross-sectional study; Level of evidence, 3. Methods: Magnetic resonance imaging scans of the knee from a sports imaging facility were screened and reviewed to identify 2 groups of patients: those with and those without imaging signs of patellar tendinopathy. The lateral radiographs were reviewed and measurements made to determine (1) lever arm ratio, (2) moment arm ratio, (3) angle between the moment and line of pull of the patellar tendon, (4) patellar tendon pivot point angle, and (5) patellar height (alta). Measurements were obtained directly from radiographs. The images and measurements were reviewed by 2 experienced orthopaedic clinicians. Results: A total of 105 patients were included in this study: 52 with patellar tendinopathy and 53 without patellar tendinopathy (controls). The mean age was similar between groups (23 years); females accounted for 8 of 52 patients with patellar tendinopathy and 24 of 53 patients without. The lever arm ratio in the group with patellar tendinopathy versus controls was 1.71 versus 1.01 ( P = .01), with a moment arm difference of 1.00 versus 0.80 ( P < .01), respectively. There was no difference detected between groups for patellar tendon angle, patellar tendon pivot point angle, knee flexion angle, or incidence of patella alta. No correlation was found with our measurements and the Insall-Salvati ratio. Statistical analysis was also performed according to sex, and a statistically significant difference between groups was found for differences in lever arm ratio and moment arm. Conclusion: The lever arm ratio and moment arm ratio from lateral radiographs were significantly different between patients with and without patellar tendinopathy. Further study is needed on the biomechanical implications of the pivot point and how altering it can affect stress within the patellar tendon, patellofemoral joint, and associated clinical outcomes.